Analysis of shallow-groundwater dynamic responses to water supply change in the Haihe River plain - Z. Lin; W. Lin; L. Pengfei (Proceedings of the International Association of Hydrological Sciences, 2015)
When the middle route of the South-to-North Water Diversion Project is completed, the water supply pattern of the Haihe River plain in North China will change significantly due to the replenishment of water sources and groundwater-exploitation control. The water-cycle-simulation model – MODCYCLE, has been used in simulating the groundwater dynamic balance for 2001–2010. Then different schemes of water supply in 2020 and 2030 were set up to quantitatively simulate the shallow-groundwater dynamic responses in the future. The results show that the total shallow-groundwater recharge is mainly raised by the increases in precipitation infiltration and surface-water irrigation infiltration. Meanwhile, the decrease of groundwater withdrawal contributes to reduce the total discharge. The recharge–discharge structure of local groundwater was still in a negative balance but improved gradually. The shallow-groundwater level in most parts was still falling before 2030, but more slowly. This study can benefit the rational exploitation of water resources in the Haihe River plain.